Monitoring Intense Oceanic Fronts Using Sea Surface Roughness: Satellite, Airplane, and In Situ Comparison. Issue 8 (19th August 2020) - Rascle, Nicolas; Chapron, Bertrand; Molemaker, Jeroen; Nouguier, Frédéric; Ocampo‐Torres, Francisco J.; Osuna Cañedo, J. Pedro; Marié, Louis; Lund, Björn; Horstmann, Jochen
Abstract: Sea surface roughness is affected by surface current gradients, which provides a means of monitoring from satellite sharp oceanic fronts. This paper is the second report of an experiment designed to compare observations of sea surface roughness and surface currents at an unprecedented accuracy, owing to the conjunction of numerous deployed drifters and roughness instruments. About 200 drifters sampled a thin 10 km elongated submesoscale front, also monitored by a high density of roughness instruments: satellite synthetic aperture radar, satellite, and airborne multiangle sunglint radiometers. The first paper focused on the retrieval of the current gradient direction (convergence and cyclonic vorticity) at the front, using roughness observations at multiple angle from airplane. This second paper focuses on the retrieval of the current gradient magnitude and scale, using roughness observations at different scales, from airplane and from satellite. Two main results are obtained: (i) Trajectories of selected drifters show that the front is only 50 m wide and unambiguously exhibits convergence and cyclonic vorticity up to 100 f (with f the Coriolis frequency). This far exceeds previously documented values for submesoscale deep ocean fronts. (ii) Correct estimation of such extreme current gradients using surface roughness hinges on instruments with sufficiently high spatial resolution. Lower‐resolution roughness sensors can still detect the front, as demonstrated from observations and a simplified model, but cannot properly estimate the current gradient magnitude and the frontal width. Those results provide guidelines for monitoring intense current gradients from space using sea surface roughness. Plain Language Summary: Ocean surface currents are not uniform horizontally but involve structures of many different sizes. After focusing on large‐scale currents (about 1, 000 km) and eddies (about 100 km), attention is nowadays turning toward fine‐scale (about 1 km) fronts and filaments. Those fine structures are indeed particularly important for the exchanges between ocean surface and deeper ocean, for the accumulation of drifting pollution, and for the concentration of biological production and marine predators. Fishermen well know that oceanic fronts can be revealed by visual inspection of the ocean surface roughness. Exploring this idea, this paper investigates how oceanic fronts can be monitored using images of sea surface roughness. Images from satellites and airplanes were taken during an experiment where hundreds of surface drifters were released and got caught within an intense front. Two new lessons are learned from those observations: (1) The front was only 50 m wide, which is much sharper than commonly assumed for fronts of this type. (2) The front is thus associated with extreme current shear, which can only be detected by roughness sensors with sufficiently high spatial resolution. Those are important findings to improve monitoring of intense oceanic fronts from satellite. Key Points: Sea surface roughness induced by a submesoscale oceanic front is measured from satellite and airplane during a drifter release experiment Drifters unambiguously show extreme frontal sharpness with extreme current gradients, including both convergence and cyclonic vorticity Accurate monitoring of such sharp front using surface roughness is demonstrated and hinges on the availability of high‐resolution sensors